MONITORING TATA KELOLA DANA DESA TAHUN 2020 KECAMATAN PULUNG KABUPATEN PONOROGO - Sudarmanto Sudarmanto (JI@P, 2021)
The birth of Law Number 6 of 2014 concerning Villages has placed the position ofthe village as a customary law community unit in accordance with the rights of theorigin of the village, so that village autonomy is recognized and respected in thegovernment system of the Unitary State of the Republic of Indonesia.Village Funds are funds sourced from the State Revenue and Expenditure Budgetallocated to Villages which are transferred through the district / city RegionalRevenue and Expenditure Budget and used to finance government administration,development implementation, community development, and empowerment. Thepurpose of this study was to determine how the effectiveness of the use of villagefunds for economic development and empowerment of rural communities in thePulung district, Ponorogo district.This research is motivated by the existence of problems related to the governanceof village funds. The level of budget absorption, but in terms of the accountabilityreport, has not carried out village financial administration properly. On the basisof these problems, this study aims to analyze the implementation of village funds in2020 in Pulung District, Regency. Monitoring theory in this study uses Dunn in(1981) that the implementation of village funds must be based on honesty and legalaccountability, process accountability, program accountability and policyaccountability.This study uses a descriptive method with a qualitative approach. Researchinformants using purposive sampling technique. Data collection techniques usingin-depth interviews and documentation. The data analysis technique used isinteractive analysis consisting of data collection, data condensation, datapresentation and conclusion drawing.Keyword: Compliance,Auditing,Accounting,Explanation